2011
DOI: 10.1371/journal.pone.0019042
|View full text |Cite
|
Sign up to set email alerts
|

Irvalec Inserts into the Plasma Membrane Causing Rapid Loss of Integrity and Necrotic Cell Death in Tumor Cells

Abstract: Irvalec is a marine-derived antitumor agent currently undergoing phase II clinical trials. In vitro, Irvalec induces a rapid loss of membrane integrity in tumor cells, accompanied of a significant Ca2+ influx, perturbations of membrane conductivity, severe swelling and the formation of giant membranous vesicles. All these effects are not observed in Irvalec-resistant cells, or are significantly delayed by pretreating the cells with Zn2+. Using fluorescent derivatives of Irvalec it was demonstrated that the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 25 publications
(29 reference statements)
4
34
0
Order By: Relevance
“…Natural product toxins such as the kahalalides induce rapid cell death, but likely oligomerize directly to form pores in cellular membranes (Molina-Guijarro et al, 2011). Honokiol is a small molecule lignan isolated from tree bark found to induce mitochondrial dysfunction and necrosis (Li et al, 2007).…”
Section: Ag311 Induces Necrosis In Breast Cancermentioning
confidence: 99%
“…Natural product toxins such as the kahalalides induce rapid cell death, but likely oligomerize directly to form pores in cellular membranes (Molina-Guijarro et al, 2011). Honokiol is a small molecule lignan isolated from tree bark found to induce mitochondrial dysfunction and necrosis (Li et al, 2007).…”
Section: Ag311 Induces Necrosis In Breast Cancermentioning
confidence: 99%
“…Finally, the membrane permeabilization assays and the morphological changes observed by phase contrast microscopy indicated that pipecolidepsin A induced a lytic process that leads to rapid necrotic cell death. Given that the cellular effects observed with pipecolidepsin A are quite similar to those detected with the structurally related compound Irvalec 37 , it is likely that these compounds share a common mechanism of action, directly interacting with the plasma membrane of tumour cells. Interestingly, the cyclodepsipeptide lacking the diol (DADHOHA) moiety did not show any cytotoxicity, thereby highlighting the relevance of the linear peptidic arm and pointing out the importance of the distinctive head-to-side-chain scaffold in the biological activity of these natural products.…”
Section: Discussionmentioning
confidence: 94%
“…Oxopyrrolidine molecules with a proline backbone have been considered for a wide range of applications such as ACE inhibitors, antibacterial, antitumor properties and applications in asymmetric catalysis [1][2][3]. The asymmetric synthesis of pyrrolidine derivatives for both biological and catalytic purposes has received signi cant attention.…”
Section: Discussionmentioning
confidence: 99%